2020
DOI: 10.1101/2020.10.28.20221630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase II Clinical trial for Evaluation of BCG as potential therapy for COVID-19

Abstract: Bacillus Calmette Guerin (BCG) is widely used in national vaccination programs worldwide. It is accepted that BCG alleviates both pathogen and allergy induced respiratory diseases that could also include Covid-19. To investigate this possibility, we randomly assigned 60 Covid-19 patients, after admission to the hospital with pneumonia and requirement for oxygen therapy in a 1:1 ratio to receive either a single adult dose of intradermal BCG or normal saline with concomitant standard of care (SoC) medications. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a recent report, administration of BCG at the time of hospital admission for COVID-19 did not raise any safety concerns. 48 In addition, there was no evidence of increased severity of COVID-19 among participants who participated in BCG trials prior to the pandemic. 49 …”
Section: Ethics and Disseminationmentioning
confidence: 94%
“…In a recent report, administration of BCG at the time of hospital admission for COVID-19 did not raise any safety concerns. 48 In addition, there was no evidence of increased severity of COVID-19 among participants who participated in BCG trials prior to the pandemic. 49 …”
Section: Ethics and Disseminationmentioning
confidence: 94%
“…Mouse studies have shown that BCG can protect against SARS-CoV-2 and influenza infection via the engagement of the innate and adaptive immune system, particularly CD4+ T helper cells [ 107 ]. Clinical trials assessing the outcome of SARS-CoV-2 infection in BCG-vaccinated individuals showed mixed results ( Table 2 ) with 10 trials and retrospective observational studies showing a protective effect (NCT04659941, NCT04369794, NCT04414267, NCT04417335, CTRI/2020/05/025013, NCT04475302, CTRI/2020/07/026668) [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ], whereas 7 trials showed no protective effect (NCT04373291, RBR-4kjqtg, NCT04328441, NCT04537663, NCT04648800, NCT04379336, NCT04327206) [ 118 , 119 , 120 , 121 , 122 , 123 ]. Each study looked at the protective effect that the BCG vaccination has for COVID-19 in different ways, and each study assessed different populations, which may explain the mixed results between trials.…”
Section: T Cell Cross-reactivity From the Bacillus Calmette–guérin Va...mentioning
confidence: 99%
“…The majority of clinical trials addressing this are currently recruiting or ongoing. To date, at least 4 have concluded and shown BCG can provide some benefit in COVID-19 (20)(21)(22)(23). Additionally, large country-level epidemiological analyses, as well as a study of > 6000 health care workers, have shown a negative correlation between BCG vaccination status, COVID-19 disease severity and SARS-CoV-2 IgG seroprevalence (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%